2013
DOI: 10.1002/bjs.9118
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of intraoperative peritoneal lavage for colorectal cancer staging

Abstract: Evidence of intraoperative peritoneal tumour cells at colorectal cancer resection is predictive of adverse cancer outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 52 publications
0
17
0
1
Order By: Relevance
“…Although the size of the patient sample was limited, several randomized studies suggested that adjuvant HIPEC may significantly improve survival and reduce the incidence rate of PC in patients with gastric cancer and CRC (22)(23)(24)(25). A positive peritoneal lavage following macroscopic curative surgery in patients with CRC appears to be associated with decreased survival and increased recurrence of PM (7)(8)(9) and HIPEC appears to be a suitable treatment for patients at high risk of PM. Thus, in our preliminary clinical study, we enrolled patients in whom complete resection of macroscopic disease was achieved prior to HIPEC.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the size of the patient sample was limited, several randomized studies suggested that adjuvant HIPEC may significantly improve survival and reduce the incidence rate of PC in patients with gastric cancer and CRC (22)(23)(24)(25). A positive peritoneal lavage following macroscopic curative surgery in patients with CRC appears to be associated with decreased survival and increased recurrence of PM (7)(8)(9) and HIPEC appears to be a suitable treatment for patients at high risk of PM. Thus, in our preliminary clinical study, we enrolled patients in whom complete resection of macroscopic disease was achieved prior to HIPEC.…”
Section: Discussionmentioning
confidence: 94%
“…However, the use of cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (HIPEC) was reported to be a novel approach to treating peritoneal surface malignancies (2)(3)(4)(5)(6). Furthermore, as a positive peritoneal lavage following macroscopic curative surgery has been associated with decreased survival, increased recurrence and peritoneal metastases (PM) (7)(8)(9), HIPEC is considered to be a viable option for the treatment of patients at high risk of developing PM.…”
Section: Introductionmentioning
confidence: 99%
“…Although very little is understood about the process of peritoneal metastasis, clinical studies indicate an involvement of tumor shedding followed by dissemination via the peritoneal or ascitic fluid current [4]. In addition, the peritoneal mesothelium and its underlying stroma must be primed by its interaction with floating cancer cells to allow cancer cell adhesion and invasive growth [7].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells detach from the primary tumor spontaneously or iatrogenically, and are transported by the peritoneal fluid [3]. Disseminated cancer cells can be found in the peritoneal fluid before surgery in 18%e25% [3,4] of the colorectal patients. After surgery this is up to 10% higher [2,5], similar results are published for pelvic cancer patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of tumor cells during lavage of GI cancers has been shown to portend a poor prognosis. [2023] Thus, there exists a need for improved treatments that may be added to existing regional and systemic therapies. It is important to emphasize that this study did not show an added benefit of WL to RFS or OS.…”
Section: Discussionmentioning
confidence: 99%